Segregation of Acetylcholine and GABA in the Rat Superior Cervical Ganglia: Functional Correlation - Elinos, Diana; Rodríguez, Raúl; Martínez, Luis Andres; Zetina, María Elena; Cifuentes, Fredy; Morales, Miguel Angel (Frontiers in Cellular Neuroscience, 2016)
Sympathetic neurons have the capability to segregate their neurotransmitters (NTs) and co-transmitters to separate varicosities of single axons; furthermore, in culture, these neurons can even segregate classical transmitters. In vivo sympathetic neurons employ acetylcholine (ACh) and other classical NTs such as gamma aminobutyric acid (GABA). Herein, we explore whether these neurons in vivo segregate these classical NTs in the superior cervical ganglia of the rat. We determined the topographical distribution of GABAergic varicosities, somatic GABAA receptor, as well as the regional distribution of the segregation of ACh and GABA. We evaluated possible regional differences in efficacy of ganglionic synaptic transmission, in the sensitivity of GABAA receptor to GABA and to the competitive antagonist picrotoxin (PTX). We found that sympathetic preganglionic neurons in vivo do segregate ACh and GABA. GABAergic varicosities and GABAA receptor expression showed a rostro-caudal gradient along ganglia; in contrast, segregation exhibited a caudo-rostral gradient. These uneven regional distributions in expression of GABA, GABAA receptors, and level segregation correlate with stronger synaptic transmission found in the caudal region. Accordingly, GABAA receptors of rostral region show larger sensitivity to GABA and PTX. These results suggest the presence of different types of GABAA receptors in each region that result in a different regional levels of endogenous GABA inhibition. Finally, we discuss a possible correlation of these different levels of GABA modulation and the function of the target organs innervated by rostral and caudal ganglionic neurons.